A new method for control of networked systems with an experimental verification. (May 2015) - Rahmani, Behrooz; Markazi, Amir H.D.; Seyfi, Behzad
Abstract: This paper presents a variable selective control methodology for control of networked systems subject to transfer delay, packet-loss and packet-disordering. This approach is based upon the extension of the variable sampling period idea with a new packet based control methodology. In this way, corresponding to a range of expected time delays, a number of step-invariant discrete-time plant models are considered and based on them, a switching observer-based controller is designed by solving linear matrix inequalities ( LMIs ). A sufficient condition for closed-loop asymptotic stability is derived. Simulation and experimental investigations demonstrate the effectiveness of the proposed method in the real world.